Search Engine Optimization for a Website (3PDigital.Co) - Joshi, Abhijeet; Vijaykumar, Suhasini (International Journal of Computer Sciences and Engineering, 2019)
In today’s world internet is growing fast day by day. data is very huge and complex. To sort this amount of data over large database search engine plays a very important role. Google is the basic search engine through which we can optimize the website. With the help of search engine, we can actively gather the visitors to our site. Search engine is the most common part of our today’s life. Because of this reason, search engines play “a prominent position in the online world”; because of this people can find any information that they want from the internet very easily. Search Engine is the most valuable asset for the company to grow their market in the current business. It increases the market value This research paper provides to improve the ranking of a website(3pdigital.co).